2020
DOI: 10.1136/bmjopen-2019-036044
|View full text |Cite
|
Sign up to set email alerts
|

What are the elements of a whole system approach to community-centred public health? A qualitative study with public health leaders in England’s local authority areas

Abstract: ObjectivesThe aim of the study was to identify key elements of whole system approaches to building healthy communities and putting communities at the heart of public health with a focus on public health practice to reduce health inequalities.DesignA mixed-method qualitative study was undertaken. The primary method was semi-structured interviews with 17 public health leaders from 12 local areas. This was supplemented by a rapid review of literature, a survey of 342 members of the public via Public Health Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…This could help j JOURNAL OF PUBLIC MENTAL HEALTH j improve multi-sector collaboration, as well as generating a more comprehensive understanding of the conditions necessary for effective programmes and policies (Langellier et al, 2019). The engagement of local stakeholders and community members could produce wider insights and support ownership and adoption of effective communitycentred solutions to public mental health challenges (Allender et al, 2015;Stansfield et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could help j JOURNAL OF PUBLIC MENTAL HEALTH j improve multi-sector collaboration, as well as generating a more comprehensive understanding of the conditions necessary for effective programmes and policies (Langellier et al, 2019). The engagement of local stakeholders and community members could produce wider insights and support ownership and adoption of effective communitycentred solutions to public mental health challenges (Allender et al, 2015;Stansfield et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Equitable, sustained improvements in population mental health, along with many other contemporary public health challenges, will not be achieved through simple, linear causal models and siloed interventions, but through complex systems approaches (Rutter et al, 2017;McManus, 2017). Public Health England (PHE) (the national public health agency) has applied such approaches within whole system work to tackle obesity (Public Health England, 2019a) and health inequalities (Stansfield et al, 2020). PHE research into universal public health approaches has identified the need to "further investigate the benefits of using complex systems mapping to facilitate a whole systems approach to children and young people's mental health to understand more about the complex interplay between factors and the benefits of adopting a whole systems approach" (Public Health England, 2019d).…”
Section: Introductionmentioning
confidence: 99%
“…While we have suggested that a breadth of support and services across Connector, Gateway, Direct and Systems approaches is important in responding to the complexities of influencers on mental health in older age (as at any age), the lack of consistent measurement of outcomes, even within categories, is a challenge for service de- Despite the UK focus and context-specific nature of funding and implementation, the broad framework, typologies, and content examples described may also be applicable beyond the UK thanks to its theoretical underpinning and 'whole system' framing (Stansfield et al, 2020).…”
Section: Recommendationsmentioning
confidence: 99%
“…Communities responded swiftly to support neighbours in need, inequalities widened at the community level and the need for a more community-oriented response became evident (South et al 2020;Lent and Studdert 2021;The Kings Fund 2021). The needed public health system change includes sustaining the practice we have seen in the pandemic to gather and respond to community insight, work alongside and support community action, foster trusting relationships to make decisions with communities, invest in a thriving voluntary and community sector, measure and value community determinants of health such as sense of belonging and community resilience and scale a range of community-centered approaches into all public health action to reduce health inequalities (Stansfield, South, and Mapplethorpe 2020).…”
Section: Mental Health Recovery and Transformation: Lessons For Actionmentioning
confidence: 99%